2000
DOI: 10.1016/s0895-7061(00)01206-1
|View full text |Cite
|
Sign up to set email alerts
|

Angioplasty of atherosclerotic and fibromuscular renal artery stenosis: Time course and predicting factors of the effects on renal function

Abstract: The effects of percutaneous transluminal renal angioplasty (PTRA) on the renal function of stenotic kidneys are usually assessed by evaluating the changes in serum creatinine, which is quite a rough indicator of glomerular filtration rate (GFR). In 27 hypertensive patients with 19 atherosclerotic and 11 fibromuscular significant renal artery stenoses, we investigated with renal scintigraphy the short-term (5 days) and long-term (10 months) effects of a technically successful PTRA (in seven cases combined with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
51
0
1

Year Published

2002
2002
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 26 publications
1
51
0
1
Order By: Relevance
“…This functional test is a highly specific tool for the detection of renal artery stenosis, renal hypoperfusion, and activation of the renin-angiotensin system 17 ; it is also a predictor of the improvement in blood pressure and renal function after revascularization. 23,24 We also observed that the rate of excreted 8-iso-PGF 2␣ was related to the difference in angiotensin II released from the hypoperfused kidney compared with the contralateral kidney.…”
Section: Minuz Et Al Oxidative Stress In Renovascular Disease 2803mentioning
confidence: 68%
“…This functional test is a highly specific tool for the detection of renal artery stenosis, renal hypoperfusion, and activation of the renin-angiotensin system 17 ; it is also a predictor of the improvement in blood pressure and renal function after revascularization. 23,24 We also observed that the rate of excreted 8-iso-PGF 2␣ was related to the difference in angiotensin II released from the hypoperfused kidney compared with the contralateral kidney.…”
Section: Minuz Et Al Oxidative Stress In Renovascular Disease 2803mentioning
confidence: 68%
“…Revascularization is effective in stabilizing or improving renal function in patients with symptomatic atherosclerotic RAS (701,(744)(745)(746)(747)(748). Several trials have documented that renal artery stent placement improves or stabilizes renal function in patients with atherosclerotic RAS (749)(750)(751)(752).…”
Section: Class Iib Percutaneous Revascularization May Be Considered Fmentioning
confidence: 99%
“…Finally, in patients with a solitary kidney or bilateral RAS, the ability of the patient to tolerate long-term administration of angiotensin antagonist medications may be facilitated by relief of a hemodynamic renal artery obstruction. Percutaneous transluminal renal balloon angioplasty is the treatment of choice for symptomatic RAS caused by FMD (744,(768)(769)(770). However, in atherosclerotic RAS, balloon angioplasty alone is associated with a lower procedural success rate and a higher restenosis rate (745,(771)(772)(773)(774)(775)(776)(777).…”
Section: Impact Of Ras On Congestive Heart Failure and Unstable Anginamentioning
confidence: 99%
“…We have recently addressed this issue by using the radioisotopic technique, which allows an accurate evaluation of the split function of the two kidneys to eliminate the limitations inherent to creatinine and creatinine clearance. Using this methodology, we have examined the short-and long-term effects of PTRA/stent implantation in 21 kidneys with ARAS and found an overall improvement of GFR in the dilated kidney of 8 ml/min (21). This increase was biphasic; half of it occurred with 1 wk after the procedure, and the remaining during the following 6 mo.…”
Section: Ptra: Effects On Renal Functionmentioning
confidence: 99%